Metacognitive Awareness and Academic Writing Performance: Evidence from Foreign Students in Indonesian Language Programs - Budiana, Nia; Suyitno, Imam; Susanto, Gatut; Malik, Agung Rinaldy (Journal of Cultural Analysis and Social Change, 2026)
Metacognitive strategies are widely recognized as central to successful second language (L2) academic writing, yet most research has focused on Anglophone contexts. This study examines how foreign learners in Indonesian language programs (Bahasa Indonesia bagi Penutur Asing—BIPA) employ metacognitive strategies in planning, monitoring, and evaluating academic writing. A qualitative case study design was applied, with data collected through semi-structured interviews with 11 intermediate-level BIPA students from Thailand, Timor Leste, Gambia, Madagascar, Pakistan, and Egypt. Data were transcribed and analyzed thematically using Braun and Clarke’s framework to identify patterns of engagement. The findings reveal three interrelated dimensions of metacognitive practice. In planning, some students demonstrated systematic goal-setting, outlining, and resource preparation, while others relied on spontaneous drafting or peer discussions. Monitoring strategies ranged from real-time self-checking for coherence and vocabulary use to reactive monitoring, where revision was deferred until after drafting, often compromising coherence. Evaluation strategies also varied: proactive learners engaged in comprehensive revision and incorporated feedback, whereas others limited evaluation to surface-level corrections. These differences were mediated by cultural orientations, linguistic proficiency, and prior academic experiences. This study extends metacognition research beyond English-dominated contexts, offering insights from Indonesian academic writing. Pedagogically, the results underscore the need for explicit instruction in metacognitive strategies within BIPA curricula, particularly in scaffolding planning and monitoring skills. The findings highlight that metacognition is not universal but contextually situated, shaped by cultural and educational traditions.